Cognitive-constructivist Approach in Medical Settings: The Use of Personal Meaning Questionnaire for Neurological Patients’ Personality Investigation - Poletti, Barbara; Carelli, Laura; Lafronza, Annalisa; Solca, Federica; Faini, Andrea; Ciammola, Andrea; Grobberio, Monica; Raimondi, Vanessa; Pezzati, Rita; Ardito, Rita B.; Silani, Vincenzo (Frontiers in Psychology, 2017)
Objective: The cognitive-constructivist psychotherapy approach considers the self as a continuos regulation process between present and past experience, in which attributions of meaning is characterized by the use of internal rules. In this conception, everyone would be driven by a specific inner coherence called Personal Meaning Organization – PMO. Such approach has never been applied to neurological patients by means of ad hoc developed tools. We performed an explorative study aimed to characterize personality styles in different neurological conditions within the theoretical framework of cognitive-constructivist model. Methods: Three groups of neurological patients (Amyotrophic Lateral Sclerosis, Multiple Sclerosis, Primary Headache) and a sample of healthy participants, each composed by 15 participants, for a total of 60 participants, were recruited. The Personal Meaning Questionnaire (PMQ), an Italian questionnaire assessing PMOs construct, and other clinical tools for psychological and quality of life assessment were administered to all subjects. Results: The main finding concerned the detection, across all clinical conditions, of a higher prevalence of phobic personality style, with Amyotrophic Lateral Sclerosis showing a relevant prevalence of such PMO with respect to all other neurological conditions and controls. However, with respect to controls, in all clinical conditions, PMQ highlighted a tendency, even if not statistically significant, to codify experience by means of specific cognitive and emotional patterns. Conclusion: Our findings represent the first contribution towards understanding the personality profiles of patients affected by neurological conditions according to cognitive-constructivist theory.